Bilateral relationship between technological changes and income inequality in developing countries - Sirine Mnif (Atlantic Review of Economics, 2016)
The work focuses on the analysis of the bilateral relationship between technological changes and inequality. First, it focus on the impact of technological innovations on inequality and the theory of Skills Biased Technological Changes (SBTC). Given technology can produce inequality; what is the impact of these inequalities on the distribution and the production technologies? Conversely, it's interested in, the transmission channels through which inequality affect technological changes. And that being said, let's enrich the interactions between inequality and technological changes. The empirical validation is based on the technique of Panel data for a sample of developing countries. The paper concludes that a positive relationship of technological changes on inequality seems to be confirmed. Increased innovation increases inequality. And a negative effect of inequality on technological changes also seems to be confirmed. Rising inequality hampers technological innovations.
Keywords: O32; O34; D31; 330; technological changes; inequality; developing countries